Effects of guanidinoacetic acid supplementation on growth performance, serum biochemical parameters, immune function, and antioxidant capacity in Xinjiang Hu sheep - Zhu, Wenshu; Liu, Jiancheng; Wang, Yakun; Mo, Xucheng; Zeng, Wenshuai; Ye, Zixuan; Liu, Mengjian (Frontiers in Animal Science, 2025)
BackgroundHu sheep, a key meat breed introduced to Xinjiang, face growth inhibition and low feed efficiency due to challenges in adapting to the cold, arid climate and drastic seasonal temperature fluctuations in northern Xinjiang. Guanidinoacetic acid (GAA), a precursor of creatine, has been shown to enhance growth performance by optimizing energy metabolism and improving health by modulating immunity and antioxidant capacity. However, research on GAA in ruminants remains limited, and few mechanistic studies have addressed nutritional regulation strategies to optimize growth performance and stress resistance of Hu sheep under the harsh climatic conditions of northern Xinjiang, particularly regarding the efficacy of Rumen-protected Guanidinoacetic acid (RPGAA) in bypassing ruminal degradation to improve production performance. This study systematically evaluated the effects of the supplements of GAA and RPGAA in diet on growth performance, serum biochemistry, immunity, and antioxidant capacity in Hu sheep, aiming to elucidate metabolic regulatory mechanisms and provide theoretical and technical support for efficient Hu sheep farming.MethodsA total of sixty-three healthy Hu rams were randomly divided into three groups, each with three replicates and seven sheep per replicate pen. The three groups were as follows: Group I (control group with basal diet), Group II (basal diet + 1.0 g/kg GAA), and Group III (basal diet + 1.0 g/kg RPGAA).ResultsCompared to the control, RPGAA increased final body weight and average daily gain (P<0.01), with a lower feed-to-gain ratio than GAA (P<0.01). Both supplements enhanced feed intake (P<0.01), but RPGAA showed superior nutrient utilization efficiency. Serum biochemical analyses revealed that RPGAA significantly elevated glucose (P<0.01), albumin (P<0.01), and albumin-to-globulin ratio (P<0.01), while reducing triglycerides (P<0.05) and cholesterol (P<0.05). GAA showed similar trends but with less pronounced effects. Immunologically, RPGAA increased IgG levels (P<0.05) and reduced pro-inflammatory cytokines (IFN-γ, IL-2; P<0.05). Antioxidant capacity improved in both groups, with RPGAA uniquely enhancing glutathione activity (P<0.05) alongside increased SOD, T-AOC, and CAT activities (P<0.05) and reduced MDA (P<0.05).ConclusionDietary supplementation with 1.0 g/kg guanidinoacetic acid (GAA) or rumen-protected GAA (RPGAA) significantly enhances growth performance, nutrient metabolism, antioxidant capacity, and immune function in Hu sheep while mitigating inflammation in northern Xinjiang region. By circumventing ruminal degradation, RPGAA demonstrates superior efficacy over conventional GAA, as evidenced by improved feed efficiency, enhanced serum biochemical profiles (e.g., glucose, albumin), elevated immunoglobulin G (IgG), and unique augmentation of glutathione (GSH) activity. These findings establish RPGAA as an innovative nutritional strategy to optimize production efficiency and stress resilience in ruminants under challenging environmental conditions, offering practical insights for high-performance sheep farming in arid and cold climates.